From the universal to the particular through intercultural united nations crime prevention law and practice - Redo Sławomir (Temida)
The article focuses on some legal and criminological counter aspects of the functionalist approach to public international law, by taking as the example United Nations crime prevention law. On this basis, the article’s author analyses the theoretical and practical meaning of cross-disciplinary concepts of the Universal and the Particular, known also in law and criminology as the General and the Specific. He emphasizes the coexistence of both concepts and their mutual reinforcement through the intercultural United Nations policy and action.